"Schools of Music, Schools of Life": a Case Study in Ílhavo - Milheiro, Maria Helena da Cruz Martins Rodrigues (2017)
This study explores the process of teaching music in the community bands in Portugal, through qualitative and quantitative methods. It is part of a case study conducted in Banda dos Bombeiros Voluntários de Ílhavo – Música Nova. The Wind Bands are secular institutions, responsible for the initial training of most wind players in Portugal.The disinterest musicological studies revealed by this reality is explained with the persistence of essentialist a cultural paradigm that excludes practices situated between academic and popular domains. It fits in a larger study comprising Philharmonic activity in the municipality of Ílhavo. My contribution is limited to the teaching and learning of music in the wind bands and to the performative activity of Banda dos Bombeiros Voluntários de Ílhavo – Música Nova throughout 2012, trying to ascertain the impact of the musical education in the wind bands in the musical life in Portugal, particularly in the training of professional musicians.